Persepsi Masyarakat dalam Mendukung Pengembangan Potensi Daya Tarik Wisata Sejarah di Desa Wisata Letvuan Maluku Tenggara - Sukirno, Pradina Anjarwaty; Lovihan, Irma F.; Renjaan, Melissa J. (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the perception of the Letvuan Tourism Village community in supporting the development of potential historical tourism attractions. The research method used is a qualitative method with data analysis using qualitative descriptive analysis. Based on the results of the study, the perception of the Letvuan village community in supporting the development of historical tourism attractions in the Letvuan Tourism Village shows an average value of 4.4 which is included in the Strongly Agree / Strongly Support category, the perception of the Letvuan village community in supporting the development of historical tourism amenities in the Letvuan Tourism Village shows an average value of 4.4 which is included in the Strongly Agree / Strongly Support category, the perception of the Letvuan village community in supporting the development of historical tourism accessibility in the Letvuan Tourism Village shows an average value of 4.0 which is included in the Agree / Support category, the perception of the Letvuan village community in supporting the development of other supporting services in historical tourism attractions in the Letvuan Tourism Village shows an average value of 4.5 which is included in the Strongly Agree / Strongly Support category. With a total recapitulation score obtained is 17.3 with an average score of 4.3. Thus, the entire community stated that they Strongly Agree or Strongly Support the Development of Potential Historical Tourism Attractions in Letvuan Tourism Village. Keyword: perception, historical tourism, Letvuan torism village